Disability and skill mismatch - Melanie K. Jones; Peter J. Sloane (Institute for the Study of Labor (IZA), 2009)
This paper integrates two strands of literature on overskilling and disability using the 2004 British Workplace Employment Relations Survey (WERS). It finds that the disabled are significantly more likely to be mismatched in the labour market, to suffer from a pay penalty and to have lower job satisfaction, the effects being stronger for the work-limited disabled. Giving workers more discretion over how they perform their work would significantly reduce these negative effects.
urn:nbn:de:101:1-200910141102
Keywords: I0; J2; J3; J7; J24; J31; 330; Skills; disability; job matching; earnings; job satisfaction; Behinderte Arbeitskräfte; Überqualifikation; Lohndifferenzierung; Arbeitsgestaltung; Arbeitszufriedenheit; Großbritannien